The establishment of art history as a discipline in Turkish universities (1870s-1960s) - Bingöl, Verda (Lisansüstü Eğitim Enstitüsü, 2023)
This thesis is a historiography of the establishment of art history education in Turkey, covering the years between the 1870s and the 1960s. It focuses on the first two institutions where art history as an academic discipline was established: Istanbul University and Ankara University, and aims to uncover the reasons, the institutions, the scholars and the historical background responsible in the discipline's establishment, in light of archival documents and accounts of the witnesses. The thesis takes the Ottoman university (Dârülfünun) and the School of Fine Arts (Sanayi-i Nefise Mektebi) as its starting point, hence the thesis starts with the 19th century, even though the establishment of the first chair related to art history dates to 1942. In the first chapter, independent art history courses held at Dârülfünun and Sanayi-i Nefise Mektebi are discussed in relation to the educational programme of the two universities and the academic background of the lecturers that held the courses. The lecturers were all autodidacts with foreign language skills, who had not received a formal art history education, and the courses reflected these: The curriculum changed with every lecturer, they taught what they found necessary, and the focus was on aesthetics, rather than a classic art history module. The consequent result of the first chapter is that these courses cannot be viewed as the forerunners of the later art history chairs. The second chapter is divided into three sections for the three art history chairs at Istanbul University: Chair of Byzantine Art, Chair of Turkish and Islamic Art and Chair of European Art, and the third chapter is on the art history department at Ankara University, Faculty of Languages and History-Geography. These chapters are ordered chronologically, and each section discusses the reasons for the establishment, the academic backgrounds of the founders and the curriculum of the particular chairs. Since all the founding professors were from England, Germany or Austria, the chapter aims to answer whether or not there was a transfer of knowledge from the founding professors' academic backgrounds to their new posts in Turkey, what the reasons behind their invitation to Turkey were, and whether there was a continuation of their tradition in the second generation of art historians. In order to answer these questions, the thesis uses a variety of research methods: A thorough analysis of secondary sources, gathering, sorting and interpreting primary sources such as official documents, correspondences and letters as archival material, and interviews with first-hand witnesses have been carried out.
Sanat tarihinin bir disiplin olarak Türkiye'deki üniversitelerde kuruluşu (1870'ler-1960'lar)
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2023
Keywords: art history; sanat tarihi; corporate history; kurumlar tarihi; Turkish education history; Türk eğitim tarihi; Turkish science history; Türk bilim tarihi